Berenstain Bears (The): get the stage fright - Berenstain, Stan (New York : Random House, 1986)
Sister Bear worries about her lines in the school play while Brother Bear has no fear. Guess who forgets the lines during the performance?
Keywords: Bears--Fiction.; Plays--Fiction.